The Effect of Teaching English Using Realia Media on Students’ Speaking Ability - Adrianty, Uchy Mukho (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
This goal of this study was to see if there was any significant effect on students’ speaking achievement after they were taught using Realia media at MTs Muhammadiyah 1 Pekanbaru. This quantitative research method used a pre-experimental design. The technique of collecting the data used total sampling. It took one class; the eighth grade as an experimental class that consisted of 12 students. The researcher administered one time of pre-test, six times of treatments, and one time of post-test. Wilcoxon Signed Rank Test was used to analyzed the data and the hypothesis testing was analyzed by using SPSS version 20.00 at the significant level of p<0.05. The mean score increased from 43.42 up to 60.92. The result of hypothesis testing showed that the significant (2-tailed) is p value=0.003 and the level of significance is if p value<0.05. It means there was a significant effect on students’ speaking achievement after they were taught by using Realia.